2012
DOI: 10.4103/2230-8210.94248
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and metabolic syndrome: The link

Abstract: Metabolic syndrome (MetS) or “Syndrome X” which is a constellation of insulin resistance, hyperglycemia, hypertension, low high-density lipoprotein cholesterol (HDL-C), and increased very-low-density lipoprotein (VLDL) and triglyceride (TG) levels. It is one of the main threats for public health in the 21st century with its associated risk of cardiovascular disease. This condition affects a major chunk of mankind. International Diabetes Federation (IDF) estimated that around 20-25% of the adult population of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…In fact, testosterone deficiency has been reported in population studies to be associated with an increase in all-cause mortality, and this has been shown to be accounted for mainly by CVD (Khaw et al 2007, Vikan et al 2009, Araujo et al 2011. Moreover, accumulating evidence suggests that testosterone deficiency is an independent cardiovascular risk factor and many recent reviews have focussed on the link between hypogonadism, MetS, T2DM and CVD (Makhsida et al 2005, Shabsigh et al 2008, Corona et al 2009, Diaz-Arjonilla et al 2009, Jones & Saad 2009, Stanworth & Jones 2009, Traish et al 2009, Zitzmann 2009a, Grossmann et al 2010, Jones 2010a,b, Muraleedharan & Jones 2010, Moulana et al 2011, Wang et al 2011, Saad et al 2012, Salam et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, testosterone deficiency has been reported in population studies to be associated with an increase in all-cause mortality, and this has been shown to be accounted for mainly by CVD (Khaw et al 2007, Vikan et al 2009, Araujo et al 2011. Moreover, accumulating evidence suggests that testosterone deficiency is an independent cardiovascular risk factor and many recent reviews have focussed on the link between hypogonadism, MetS, T2DM and CVD (Makhsida et al 2005, Shabsigh et al 2008, Corona et al 2009, Diaz-Arjonilla et al 2009, Jones & Saad 2009, Stanworth & Jones 2009, Traish et al 2009, Zitzmann 2009a, Grossmann et al 2010, Jones 2010a,b, Muraleedharan & Jones 2010, Moulana et al 2011, Wang et al 2011, Saad et al 2012, Salam et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…48 Moreover, in a study by Brand and colleagues, 49 higher SHBG levels were associated with a reduced risk of developing MetS. Given that higher levels of SHBG are associated with lower levels of testosterone, a non-linear relationship between SHBG, MetS and testosterone exists.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that testosterone deficiency leads to increased fat deposition, whereas high testosterone levels inhibit adipocyte development, promoting lipolysis and reducing fatty acid synthesis (Salam et al 2012). In normal sperm, DHT was able to reduce triglyceride content, while it induced lipase and acyl-CoA dehydrogenase activities, suggesting a lipolytic effect.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we observed a reduced response to DHT in varicocele sperm; therefore, it could be speculated that varicocele sperm are affected by a dismetabolic syndrome due to inefficacious enzymatic activities leading to the accumulation of triglycerides. Accordingly, a strong association of testosterone with lipogenesis has been observed at the systemic level during dismetabolic syndrome (Salam et al 2012). Although the regulation of sperm energy metabolism is not well known, it may be generalized that uncapacitated sperm are associable with an anabolic metabolism, while capacitation with a catabolic metabolism.…”
Section: Discussionmentioning
confidence: 99%